Réponses

2014-09-07T20:33:14+02:00
P(n): 0^2+1^2+2^2+...+n^2=n(n+1)(2n+1)/6

0^2=0*(0+1)(2*0+1)/6
0^2+1^2=1=1*(1+1)(2*1+1)/6

0^2+1^2+3^2+...+n^2+(n+1)^2 = [0^2+1^2+3^2+...+n^2]+(n+1)^2
Si P(n) est vrai alors
0^2+1^2+3^2+...+n^2+(n+1)^2 = n(n+1)(2n+1)/6+(n+1)^2
=(n^2+n)(2n+1)/6+n^2+2n+1
=(2n^3+n^2+2n^2+n)/6+n^2+2n+1
=(2n^3+3n^2+n+6n^2+12n+6)/6
=(2n^3+9n^2+13n+6)/6
Or (n+1)((n+1)+1)(2(n+1)+1)=(n+1)(n+2)(2n+3)=(n^2+3n+2)(2n+3)=2n^3+3n^2+6n^2+9n+4n+9=2n^3+9n^2+13n+6
On peut ainsi déduire que
0^2+1^2+2^2+...+n^2+(n+1)^2=(n+1)((n+1)+1)(2(n+1)+1)/6
CQFD
Merci bcq vraiment j'étais loin de trouver la solution bye bye
Avec plaisir!